PERANANAN ORANGTUA DALAM MENSOSIALISASIKAN NILAI AGAMA REMAJA MUSLIM DI KELURAHAN TANGKERANG UTARA KECAMATAN BUKIT RAYA KOTA PEKANBARU - Sinta, Nur Tiara; Tantoro, Swis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This research was conducted to determine how the parents’ role in providing education in religious values to their children within the scope of the family. Where the family is the main institution that becomes a kid in accepting socialization, both in terms of affection, protection and education materials as well as either formal or informal. Education that had given also not spared from the scope of the religion embraced by the family. In the research the researcher took informant Islamic religion, to know how parenting and socialization family in giving the religious values to teenagers Muslims in the Tangkerang Utara area of Bukit Raya Pekanbaru, the researcher collecting the data in advance using interview techniques directly to the informant, and also use a list of questions that had been prepared in advance, as well as observation, sampling informants using purposive sampling technique that researcher took informant intentionally and directly that have requirements (criteria, traits, characteristics, traits) which has been determined beforehand. In summary the results of this study is the parents’ role has not been fully implemented well in disseminating religious values at home, because there are still many parents who are indifferent and give the role to other institutions, this is done because some of the considerations of the parents who do not have much time to take care of and providing religious instruction for their children at home, due to busy earning a living and so on. But there are also parents who teach their own religious education to their children though rarely, because parents want to assume a direct role in shaping children's personalities who know and understand about religious values. This happens because there are parenting socialization different from each informant's parents, namely the decline of values and norms in terms of religious education, and became a decisive influence on how the child's behavior in the behavior of religion both at home and in the community. Based on this research, either directly or not parents have a very large role in shaping the character and values of the child's personality. Because whether good or not the children in the community depends on the pattern of a given student's parents. So that people judge a reflection of the child's parents, if the parents are well educated with children will be good, and vice versa.Keywords: roles, socialization patterns, religious values, child behavior